Overview of a Large Scale Carbon Capture, Utilization, and Storage Demonstration Project in an Active Oil Field in Texas, USA. (July 2017) - Balch, Robert; McPherson, Brian; Grigg, Reid
Abstract: The Southwest Regional Partnership on Carbon Sequestration (SWP) is one of seven large scale CO2 sequestration projects sponsored by the U.S. Department of Energy. The primary objective of the SWP effort, currently in its demonstration stage, is to exhibit and evaluate an active commercial-scale carbon capture, utilization and storage (CCUS) operation, and demonstrate associated effective site characterization, monitoring, verification, accounting, and risk assessment. The SWP has monitored storage of 461, 040 metric tonnes of CO2 between October, 2013 and June, 2016 into 16 active patterns. At least 1 million metric tonnes of CO2 will be stored prior to completion of the study. The SWP project is located within an active EOR field, a mature waterflood in the Farnsworth Unit, Texas, which is undergoing conversion to a CO2 flood. All CO2 utilized by the project is anthropogenic, sourced from a fertilizer and an ethanol plant, and this CO2 would otherwise be vented to the atmosphere. Much of the injected CO2 will be trapped permanently in the subsurface, and a primary objective is to quantify CO2 storage capacity and study conditions and characteristics that promote trapping. This project will contribute to the development of future commercial CCUS projects in the United States by demonstrating all aspects of an actual commercial CCUS field operation, including effective reservoir engineering, monitoring, and simulation technologies. The project has acquired multiple data sets for site characterization, monitoring CO2 plume growth, and storage security. Surface and near-surface monitoring methods used to evaluate CO2 migration out of the reservoir, have verified that CO2 leakage to the surface and/or groundwater has not occurred through September of 2016. As the SWP acquires data for each major area of study (characterization, monitoring, simulation, and risk), information and feedback are acquired to improve the work in other focus areas. A conscious effort is made to discern aspects of the work that can contribute to Department of Energy Best Practices Manuals for carbon sequestration, in particular as it relates to CCUS projects. This paper presents the SWP project, its current status, and progress towards primary goals.